2005
DOI: 10.1088/0264-9381/22/7/015
|View full text |Cite
|
Sign up to set email alerts
|

A freely falling frame at the interface of gravitational and quantum realms

Abstract: Abstract.I briefly argue for logical necessity to incorporate, besides c,h, two fundamental length scales in the symmetries associated with the interface of gravitational and quantum realms. Next, in order to clear the proverbial bush, I discuss the CPT and indistinguishability issue related to recent non-linear deformations of special relativity and suggest why algebraically well-defined extensions of special relativity do not require non-linear deformations. That done, I suggest why the stable Snyder-Yang-Me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 62 publications
0
31
0
Order By: Relevance
“…The most convincing general arguments for changes to the basic commutators are perhaps those of Ahluwalia-Khalilova [13] based on the work of Mendes, Chryssomalakos and…”
Section: Effects Of Quantum Gravitymentioning
confidence: 99%
“…The most convincing general arguments for changes to the basic commutators are perhaps those of Ahluwalia-Khalilova [13] based on the work of Mendes, Chryssomalakos and…”
Section: Effects Of Quantum Gravitymentioning
confidence: 99%
“…On top of this, spacetime in SPHA requires two new length scales, one in the extreme short distance range, the other on the cosmological scale. We denote these new length scales ℓ p and ℓ c respectively (following the notation used in [7]). …”
Section: Exemplary Osid Stylementioning
confidence: 99%
“…However, in the work presented here such resulting modifications to the quantum and spacetime structure arise not as an ad hoc speculation but from the Principle of Lie Algebraic stability. The reader is referred to [21,22,23,5,7,24] for additional discussion of these and related issues.…”
Section: Exemplary Osid Stylementioning
confidence: 99%
See 1 more Smart Citation
“…In Ref's [10], [11] (resting on the principles of the deformation idea) it is shown that the Lie algebra for the interface of the gravitational and quantum realms is the stabilized form of the Poincaré-Heisenberg algebra which carries three additional parameters and one from them is the fundamental length. It is shown that the stable Snyder-Yang-Mendes Lie algebra is a serious candidate for the symmetries underlying freely falling frames at the interface of quantum and gravitational ideas.…”
Section: Fundamental Lengthmentioning
confidence: 99%